Frequency of zinc deficiency in patients with simple febrile seizures - Shah, Sulaiman; Ullah, Kiramat; Khan, Abbas Ali (International Journal of Pathology, 2025)
Background: Febrile seizures (FS) are among the most common pediatric emergencies. Zinc, a trace element crucial for neurodevelopment and inhibitory neurotransmission, has been implicated in seizure susceptibility. Zinc deficiency may predispose children to seizures during febrile illness. Data on its frequency in children with FS are limited in our local population.Methods: This cross-sectional study was conducted in the Pediatrics Department, Mardan Medical Complex, over six months. A total of 149 children (3–60 months) presenting with simple FS (generalized seizure <15 minutes, occurring once in 24 hours) were enrolled by non-probability consecutive sampling. Children with prior afebrile seizures, epilepsy, CNS infections, recent zinc therapy, electrolyte disturbances, or focal/complex seizures were excluded. Blood samples collected after initial stabilization of seizure were analyzed for serum zinc by colorimetric method within six hours of collection; zinc deficiency was defined as <70 μg/dL. Demographic, socioeconomic, and seizure-related data were recorded. Frequencies and percentages were calculated, and associations tested using chi-square with p≤0.05 as significant.Results: Mean age was 26 ± 15 months, with 60% males; mean weight was 12.0 ± 4.1 kg. Median seizure duration was 4 minutes. Zinc deficiency was detected in 80 of 149 patients (53.7%). Age, gender, weight, seizure duration, family history of FS, and residence showed no significant association with zinc status. However, zinc deficiency was significantly more frequent in children from lower socioeconomic backgrounds (p=0.03) and with less-educated parents (p=0.04).Conclusions: These findings highlight the potential role of zinc insufficiency in FS pathogenesis. Screening and nutritional interventions may be beneficial, though randomized trials are required to confirm preventive effects of supplementation.